About millets and beans, words and genes. (15th June 2020) - Robbeets, Martine; Wang, Chuan-Chao
Abstract: Abstract : In this special collection, we address the origin and dispersal of the Transeurasian languages, i.e. Japonic, Koreanic, Tungusic, Mongolic and Turkic, from an interdisciplinary perspective. Our key objective is to effectively synthesize linguistic, archaeological and genetic evidence in a single approach, for which we use the term 'triangulation'. The 10 articles collected in this volume contribute to the question of whether and to what extent the early spread of Transeurasian languages was driven by agriculture in general, and by economic reliance on millet cultivation in particular.